The urban-rural divide in police trust: insights from Kenya - Elfversson, Emma (Policing and society, 2024)
The police occupy a central role in the functioning of the state by being tasked with upholding security, law and order. Across the African continent, the public has little trust in the police, but such perceptions are subject to considerable subnational variation. In this study, we are interested in how the different contexts in which the police operate affect police-citizen relations. We ask: How does an urban versus rural environment shape citizens’ trust in the police? We address this question within the context of Kenya, using geocoded survey data from Afrobarometer. We theorise that the rural versus urban environment will shape citizens’ experience with the police in ways that affect their attitudes toward the police. Specifically, we argue that in a context where the police have frequently been employed to repress specific sociopolitical groups, urban residents, living in denser and more diverse environments compared to rural residents, are more prone to have first- or second-hand experiences of the police that result in diminished trust towards them. Our results support these propositions: We find a strong and robust relationship between urban residence and lower levels of trust in the police. The relationship holds when controlling for respondents’ political alignment, which likely conditions people’s perceptions of state institutions. Qualitative evidence from interviews provide additional understanding of the urban-rural divide we identify. Our results provide important insights into the contextual dynamics that shape individuals’ trust in the police, and underline the importance of efforts to improve police-community relations in urbanising contexts.